Wykorzystanie analizy Procrustesa w przypadku wielu wyników skalowania wielowymiarowego - Zaborski, Artur (Utilizing Procrustes Analysis for Many Results of Multidimensional Scaling, 2006)
Procrustes analysis is a technique of matching one configuration of points obtained from multidimensional scaling analysis to another configuration obtained from a different analysis. The article presents generalized Procrustes analysis which transforms many individual configurations at the same time so that each configuration matches all others as closely as possible.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 43-49